TINJAUAN HUKUM POSITIF TERHADAP APLIKASI IJÀRAH MUNTAHIYAH BI AL-TAMLIK (IMBT) PADA PERBANKAN SYARI’AH - Muh. Baehaqi (istinbath, 2013)
Ijàrah Muntahiyah Bi al-Tamlìk is a combination of the two contract: lease contract (ijàrah) and sale and purchase contract (bai‘). Ijàrah contract with ownership at the end is one of the favorite products and is recognized by the Majlis Ulama Indonesia through its National Fatwa Council of Sharia. This paper aims to compare the concept of Ijàrah Muntahiyah Bi al-Tamlìk with those of contracts prescribed by state laws in Indonesia. It argues that any purchase agreement on the principle of hire purchase between Shariá-based banks and their customers will not use a fixed, but lose rule of treaty/contract (Treaty Innominaat), because it is not regulated by the Civil Code. In case this contract/agreement may trigger disputes between the parties in the future, the settlement is arbitrarily decided by the parties who must agree between themselves on whichever rules may apply and work for them, as this is regulated in Article 1338 (1) Civil Code.